El género en las ciencias sociales - Cobo Bedia, Rosa (Cuadernos de Trabajo Social, 2005)
In this text, gender is analysed as a category of feminist analysis which has widened the limits of objectivity in social sciences and in the same way we are warned against that process which consists of detaching the gender from feminism. The idea of gender, coined in the heart of feminism in the 70s, is one of the central concepts of the feminist paradigm and it has become an irrefutable scientific parameter in the social sciences.